TINDAKAN OPERASI THT-KL DI BLU RSUP PROF DR. R.D. KANDOU MALALAYANG - Ramschie, Meydi; Pelealu, Olivia C.; Tumbel, R. E. C. (Universitas Sam Ratulangi, 2015)
Abstract: The ear, nose, and throat (ENT) are vulnerable to virus and germ infections, pollution, and radiation. This study aimed to determine the ENT diseases accompanied by surgery and the types of operation. This was a descriptive retrospective study. The results showed that most of the diagnosis of the diseases during the year 2010-2012 was larynx tumor surgery (8.7%) and the type of operation was FESS (16.3%). In 2010 operation was performed in 40% of patients, 2011 in 37.8% and 2012 in 22.2%, and most patients were Jamkesmas (35.6%). Analysis of 2010 data showed that most patients were males (72.2%), with post tracheostomy related to laringeal tumor (11.1%), the type of operation was FESS (19.4%), and most patients were Jamkesmas (50%). Analysis of 2011 data showed that most patients were males (67.6%), with laringeal tumor (17.6%), the type of operation was FESS (17.6%), and most patients were Askes (41.2%). Analysis of 2012 data showed that most patients were males (75%), with left nasal polyps and chronic tonsillitis (each 10%) the type of operation was FESS with general anesthesia (15%), and most patients were without insurance (30%). Conclusion: In this study, most patients were males with laryngeal tumor, and most of them used Jamkesmas insurance.Keywords: ENT diseases, diagnosis, surgeryAbstrak: Organ telinga, hidung dan tenggorokan rentan terhadap infeksi virus dan kuman penyakit, polusi, serta radiasi. Penelitian ini bersifat deskriptif retropektif untuk mendapatkan penyakit-penyakit THT yang disertai tindakan operasi dan tindakan operasi yang dilakukan. Hasil penelitian menunjukkan bahwa sebagaian besar diagnosis penyakit yang dilakukan tindakan operasi selang tahun 2010-2012 yang terbanyak ialah tumor laring (8,7%) dengan jenis tindakan FESS (16,3%). Pada 2010 tindakan operasi dilakukan pada 40% pasien; 2011 sebesar 37,8 %; dan 2012 sebesar 22,2 %, dengan pasien terbanyak dari jamkesmas (35,6%). Analisis data 2010, menunjukkan terbanyak pasien laki-laki (72,2%), diagnosis penyakit pasca trakeostomi ec. tumor laring (11,1%), tindakan operasi FESS (19,4), dengan pasien terbanyak dari jamkesmas (50%). Analisis data 2011 menunjukkan terbanyak pasien laki-laki (67,6%), diagnosis tersering tumor Laring (17,6%), tindakan operasi paling sering FESS (17,6%), dengan pasien terbanyak dari Askes (41,2%). Analisis data 2012 menunjukkan paling banyak pasien laki-laki (75%), jenis operasi polip nasi sinistra dan tonsilitis kronik (masing-masing 10%) dan jenis operasi FESS + GA (15%), serta paling banyak pasien umum (30%). Simpulan: Pada studi ini tindakan operasi THT-KL yang dilakukan paling sering pada laki-laki, diagnosis terbanyak ialah tumor laring, dan sebagian besar pasien menggunakan Jamkesmas.Kata kunci: penyakit-penyakit THT, diagnosis, tindakan operasi